A long period grating-based chemical sensor insensitive to the influence of interfering parameters - James, Stephen W.; Korposh, Sergiy; Lee, Seung-Woo; Tatam, Ralph P. (Optical Society of America (OSA), 2014)
An optical fibre chemical sensor that is insensitive to interfering parameters including temperature and surrounding refractive index is described. The sensor is based upon a Mach-Zehnder interferometer formed by a pair of identical cascaded long period gratings (LPGs), with the entire device coated with a mesoporous coating of silica nanoparticles. A functional material is infused only into the coating over the section of optical fibre separating the LPGs. The transmission spectrum of the device consists of a channeled spectrum arising from interference of the core and cladding modes within the envelope of the LPG resonance band. Parameters such as temperature, strain and surrounding refractive perturb the entire device, causing the phase of the channeled spectrum and the central wavelength of the envelope shift at the same rate. Exposure of the device to the analyte of interest perturbs only the optical characteristics of the section of fibre into which the functional material was infused, thus influencing only the phase of the channeled spectrum. Measurement of the phase of the channeled spectrum relative to the central wavelength of the envelope allows the monitoring of the concentration of the analyte with no interference from other parameters.